(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Maintaining proper posture is a crucial aspect of physical health, particularly in adolescents preparing for military service. This study explores the impact of pedagogical and psychological approaches on postural correction and physical readiness in young recruits. The research involved anthropometric measurements, physical fitness tests, and psychological assessments. The results indicate a significant improvement in postural stability, self-confidence, and motivation among participants who underwent targeted training programs. This study highlights the importance of integrating educational and psychological strategies in military training preparation to enhance physical endurance and psychological resilience.